Production Economics : Evaluating Costs of Operations in Manufacturing and Service Industries - Desai, Anoop; Mital, Aashi; Taylor and Francis (Boca Raton, FL : CRC Press, an imprint of Taylor and Francis, 2018)
This book will serve a unique purpose within the world of production engineering. It will cover the economics of modern manufacturing and focus on examining the techniques and methods from a cost perspective. Additionally, it will deal with the computation of direct and indirect cost for manufacturing operations, including a variety of overhead operations in such an environment. Costing of manufacturing methods such as casting, forging, turning, milling, and welding is addressed along with inventory analysis and MRP costing. Related topics such as equipment replacement, comparison of alternatives, depreciation, buy versus make decisions, interest factors and equivalence are covered as well.
Interest Factors, Equivalence, Present Worth, Annualized Equivalent Worth, and Future worth Analysis. Cost Estimation. Materials Costing. Process Costing. Overhead Expenses. Estimation of Capital Cost and Operating Cost. Costing of Material Handling Operations. Inventory Analysis and Costing. Administrative and Facilities Costs. Establishing the Selling Price. Comparison of Alternatives. Breakeven and Benefit Cost Analysis. Depreciation. Replacement Analysis. The Make v/s Buy Decision. Vendor Selection and Vendor Cost Verification. Influence of Assembly Automation and Market Factors on Production Economics. Appendix.
Includes bibliographical references and index.
Also available in print format.
Keywords: TECHNOLOGY & ENGINEERING / Industrial Design / General; BUSINESS & ECONOMICS / Economics / General; Manufacturing industries -- Costs; Service industries -- Costs; Production engineering -- Estimates; Electronic books